PRELIMINARY STUDY FEASIBILITY OF FORMATIVE ASSESSMENT INSTRUMENTS FOR MEASUREMENT MATERIAL IN GRADE X BASED ON THE MERDEKA CURRICULUM: STUDI PENDAHULUAN KELAYAKAN INSTRUMEN ASESMEN FORMATIF MATERI PENGUKURAN KELAS X BERBASIS KURIKULUM MERDEKA - Annisa Yumna; Agus Setyo Budi; Upik Rahma Fitri (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2025)
This study aims to design the evaluation of the suitability of formative assessment instrument developed for topic of measurement in tenth-grade within the context of Kurikulum Merdeka. Kurikulum Merdeka is the continuation of the curriculum implemented during the COVID-19 pandemic, emphasizing flexibility, student empowerment, and engagement in active classroom learning, thus requiring suitable assessments for in-class learning evaluation. The form of this research is Research and Development (R&D) study. The Borg & Gall model research model will be used with both qualitative and quantitative approaches, following the stages from collecting information from physics teachers at high school which implements Kurikulum Merdeka and related previous studies, planning stage by creating analysis of Kurikulum Merdeka, relevant materials for the topic of measurement, and indicators for the formative assessment, then developing the preliminary form of the product by making the formative assessment, until the preliminary field testing stage (initial field testing and revision) by validation of the instruments involving experts then testing to the tenth-grade students until the instrument is considered suitable. The instrument is to be evaluated based on criteria including validity, reliability, level of difficulty, and discrimination power.